The functional role of CST1 and CCL26 in asthma development - Angela Hoyer; Sandip Chakraborty; Ingrid Lilienthal; Jon R. Konradsen; Shintaro Katayama; Cilla Söderhäll (Immunity, Inflammation and Disease, 2024)
Abstract Background Asthma is the most common chronic disease in children with an increasing prevalence. Its development is caused by genetic and environmental factors and allergic sensitization is a known trigger. Dog allergens affect up to 30% of all children and dog dander‐sensitized children show increased expression of cystatin‐1 (CST1) and eotaxin‐3 (CCL26) in nasal epithelium. The aim of our study was to investigate the functional mechanism of CST1 and CCL26 in the alveolar basal epithelial cell line A549. Methods A549 cells were transfected with individual overexpression vectors for CST1 and CCL26 and RNA sequencing was performed to examine the transcriptomics. edgeR was used to identify differentially expressed genes (= DEG, |log2FC | ≥ 2, FDR < 0.01). The protein expression levels of A549 cells overexpressing CST1 and CCL26 were analyzed using the Target 96 inflammation panel from OLINK (antibody‐mediated proximity extension–based assay; OLINK Proteomics). Differentially expressed proteins were considered with a |log2FC| ≥ 1, p < .05. Results The overexpression of CST1 resulted in a total of 27 DEG (1 upregulated and 26 downregulated) and the overexpression of CCL26 in a total of 137 DEG (0 upregulated and 137 downregulated). The gene ontology enrichment analysis showed a significant downregulation of type I and III interferon signaling pathway genes as well as interferon‐stimulated genes. At the protein level, overexpression of CST1 induced a significantly increased expression of CCL3, whereas CCL26 overexpression led to increased expression of HGF, and a decrease of CXCL11, CCL20, CCL3 and CXCL10. Conclusion Our results indicate that an overexpression of CST1 and CCL26 cause a downregulation of interferon related genes and inflammatory proteins. It might cause a higher disease susceptibility, mainly for allergic asthma, as CCL26 is an agonist for CCR‐3‐carrying cells, such as eosinophils and Th2 lymphocytes, mostly active in allergic asthma.